"The role of local radio programs to raies awarenes of a housewife "Tlemcen radio mode - wassila, Loucif (Journal of Humanities & Social Sciences, 2019)
This research work aimed to identify the role of local radio programs (Tlemcen) to raise awareness of a housewife. in order to reach this purpose, the study relied on qualitative appraoch and a content analysis tool was used for Tlemcen radio programs; fourteen programs had been chosen directed to the houswife.The study reached a number of results mainly the content of local radio programs which have big role of the awarness process and these selected programs were chosen by purpose. According to these categories, it had been clarified that the local dialect in the morning time & the use of music as breaks have big role in the awarness process. The results showed that the local radio programs reproduced the same situation of women in the algerian society where men are always dominant. In the light of the results of this study, I presented a set of suggegtions and recomendations mainly the interest to the environmental awarness process in the local radio programs.